Understanding Cultural Neuroscience and Ethnopsychopharmacology Can Enhance Cultural Competency in Psychiatric Nursing - Parry, Nicola (MD Conference Express, 2015)
Due to the increasing cultural and ethnic diversity of clients, psychiatric nurses must be culturally competent to be good clinical providers. This article discusses results from research in the fields of cultural neuroscience and ethnopsychopharmacology, demonstrating how cultural differences influence the neurobiological foundations of key issues in psychiatric nursing.